Optimal Phase Arrangement of Distribution Transformers for System Unbalance Improvement and Loss Reduction - Chia-Sheng Tu; Ming-Tang Tsai (Energies, 2020)
This paper presents an efficient strategy for transformer planning to reduce the system losses by means of transformer rearrangement. The customer connected to the distribution transformer are first investigated by the field survey, and the loads of the various customers are collected from the customer information system (CIS) and distribution database system (DAS) to derive their load patterns. The objective function is to minimize the total line loss in the 24 intervals. An improved bacterial foraging algorithm (IBFO) is proposed herein to find the optimal phase combination of distribution transformers to minimize the total line loss by considering operating constraints. A three-phase load flow program with Eeuivalent current injection (ECT) is used to solve the total line loss and system unbalance factor on a Taipower distribution system. The results can help operators not only perform the proper installation phase selection of distribution transformers, but also reduce the system losses, decrease the system unbalance factor, and improve the voltage profiles of the buses.